Impact of different interventions on preventing suicide and suicide attempt among children and adolescents in the United States: a microsimulation model study - Zhang, Chengchen; Zafari, Zafar; Slejko, Julia F.; Camelo Castillo, Wendy; Reeves, Gloria M.; dosReis, Susan (Frontiers in Psychiatry, 2023)
Introduction Despite considerable investment in suicide prevention since 2001, there is limited evidence for the effect of suicide prevention interventions among children and adolescents. This study was to estimate the potential population impact of different interventions in preventing suicide-related behaviors in children and adolescents. Methods A microsimulation model study used data from national surveys and clinical trials emulated the dynamic processes of developing depression and care-seeking behaviors among a US sample of children and adolescents. The simulation model examined the effect of four hypothetical suicide prevention interventions on preventing suicide and suicide attempt in children and adolescents : 1: Reduce untreated depression by 20%, 50%, and 80% through depression screening; 2: Increasing proportion of acute-phase treatment completion to 90% (i.e., reduce treatment attrition); 3: Suicide screening and treatment among the depressed individuals; 4: Suicide screening and treatment to 20%, 50%, and 80% of individuals in medical care settings. The model without any intervention simulated was the baseline. We estimated difference in suicide rate and risk of suicide attempt in children and adolescents between baseline and different interventions. Results No significant reduction in the suicide rate was observed for any of the interventions. Significant decrease in the risk of suicide attempt was observed for reducing untreated depression by 80%, and for suicide screening to individuals in medical settings: 20% screened: -0.68% (95% credible interval (CI): -0.87%, -0.55%), 50% screened: -1.47% (95% CI: -1.61%, -1.77%), 80% screened: -2.89% (95% CI: -4.57%, -2.31%). Combined with 90% completion of acute-phase treatment, risk of suicide attempt changed by -0.33% (95% CI: -0.92%, 0.04%), -0.56% (95% CI: -1.06%, -0.17%), -0.78% (95% CI: -1.29%, -0.40%) for reducing untreated depression by 20%, 50% and 80%, respectively. Combined with suicide screening and treatment among the depressed, risk of suicide attempt changed by -0.27% (95% CI: -0.dd%, -0.16%), -0.66% (95% CI: -0.90%, -0.46%), -0.90% (95% CI: -1.10%, -0.69%) for reducing untreated depression by 20%, 50% and 80%, respectively. Conclusion Reducing undertreatment (the untreated and drop-out) of depression and suicide screening and treatment in medical care settings may be effective in preventing suicide-related behaviors in children and adolescents.